The Role of Derivatives in Hedge Funds: A Comprehensive Review of Their Speculative Nature - Tanti Sugiharti; Mario Agustino Repu Nono (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review explores the speculative nature of derivatives in hedge funds, analyzing their dual role as instruments for both risk management and speculative trading. The review synthesizes findings from recent studies to highlight how hedge funds utilize derivatives not only to hedge against market fluctuations but also to engage in speculative strategies aimed at maximizing profits. This behavior raises concerns about the potential for increased market volatility and systemic risk, particularly in light of the behavioral biases influencing hedge fund managers’ decision-making processes. The analysis reveals a trend where overconfidence and herd behavior can lead to aggressive derivative trading practices, exacerbating market instability. Additionally, the review emphasizes the need for regulatory frameworks that balance innovation and risk management in the derivatives market. The findings underscore the complexities surrounding the use of derivatives in hedge funds and their implications for financial markets, calling for further research to understand these dynamics better. Ultimately, this review provides a comprehensive overview of the current state of knowledge on derivatives in hedge funds and identifies areas for future investigation.